2016
DOI: 10.1016/j.ijcard.2016.06.158
|View full text |Cite
|
Sign up to set email alerts
|

An injectable capillary-like microstructured alginate hydrogel improves left ventricular function after myocardial infarction in rats

Abstract: Background A new post–myocardial infarction (MI) therapy is injection of high-water content polymeric biomaterial gels (hydrogels) into damaged myocardium to modulate cardiac negative remodeling and preserve heart function. Methods We investigated the therapeutic potential of a novel gelatinized alginate hydrogel with a unique microstructure of uniform capillary-like channels (termed Capgel). Shortly (48 hours) after induced anterior MI, Sprague Dawley rats received intramyocardial injection of Capgel direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 23 publications
(42 reference statements)
0
20
0
1
Order By: Relevance
“…After one month, Capgel TM was observed as being well-received by the host tissue, having been infiltrated by host cells, blood vessels and containing a collagen matrix. [18] The patent capillaries in Capgel TM provide a reservoir for soluble factors and wound exudate as well as surface area for host cell adhesion, migration and differentiation. The volumizing ability of Capgel TM aids in limiting wound contracture, thus providing a larger granulation bed more consistent with the original volume of the affected site.…”
Section: Introductionmentioning
confidence: 99%
“…After one month, Capgel TM was observed as being well-received by the host tissue, having been infiltrated by host cells, blood vessels and containing a collagen matrix. [18] The patent capillaries in Capgel TM provide a reservoir for soluble factors and wound exudate as well as surface area for host cell adhesion, migration and differentiation. The volumizing ability of Capgel TM aids in limiting wound contracture, thus providing a larger granulation bed more consistent with the original volume of the affected site.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the injected hydrogel was vascularized and populated by CD68 + macrophages. These macrophages largely showed an M2-like phenotype as marked by CD206 expression, suggesting a constructive remodeling response [86]. Similar local tissue responses have been observed in disease models treated with decellularized matrix materials [26, 28, 87].…”
Section: New Strategies In Materials Designmentioning
confidence: 71%
“…Rocca et al have fabricated a gelatinized alginate hydrogel with uniform capillary-like channels and directly injected this hydrogel into the antero-septal wall at the infarct border zone [86]. Cardiac function was improved compared to saline injection control in a rat injection trial.…”
Section: New Strategies In Materials Designmentioning
confidence: 99%
“…Therefore, there are many scholars who have developed other natural hydrogels and studied their role in promoting cardiovascular disease repair to replace ECM. Currently developed hydrogels biomaterials include chitosan natural hydrogels (Li J. et al, 2013), hyaluronic acid hydrogels (Yoon et al, 2009), sodium alginate hydrogels (Rocca et al, 2016), and so on. As an immunological linear neutral polysaccharide, hyaluronic acid has multiple acid and hydroxyl groups in the molecule, which can be modified into different forms of hydrogels, including soft or hard hydrogels, as well as nanoparticles and electrospinning.…”
Section: Natural Hydrogelmentioning
confidence: 99%
“…In addition, the easily degradable, non-toxic sodium alginate hydrogel can be modified without modification and induced specific properties for a wide range of applications (Hadley and Silva, 2019). Once the degradable alginate hydrogel was designed to own a microstructure to sustain the release of angiopoietin, it can promote cardiac repair (Rocca et al, 2016) and that is why it widely used in cardiac engineering (Ruvinov and Cohen, 2016). According to the rapid development of alginate hydrogel, a multicenter prospective randomized controlled trial called AUGMENT-HF followed up for 1 year was conducted and found that patients with advanced heart failure (HF) using calcium alginate-injected hydrogel presented better cardiac function and clinical outcome rather than who accepting clinical standard medicine therapy (SMT) (Mann et al, 2016).…”
Section: Natural Hydrogelmentioning
confidence: 99%